Formal Elements of Art Products Indicate Aspects of Mental Health - Pénzes, Ingrid; van Hooren, Susan; Dokter, Ditty; Hutschemaekers, Giel (Frontiers in Psychology, 2020)
Abstract Formal elements are often used in art therapy assessment. The assumption is that formal elements are observable aspects of the art product that allow reliable and valid assessment of clients’ mental health. Most of the existing art therapy assessment instruments are based on clinical expertise. Therefore, it is not clear to what degree these instruments are restricted to formal elements. Other aspects might also be included, such as clinical expertise of the therapist. This raises the question of whether and how formal elements as observable aspects of the art product are related to clients’ mental health. To answer this question, four studies are presented that look at: 1) a meta-theoretical description of formal elements; 2) operationalization of these formal elements so they can be analyzed reliably in clients’ art products; 3) establishment of reliable and clinically relevant formal elements; 4) the relationship between formal elements and adult clients’ mental health. Results show that the combination of the formal elements “movement”, “dynamic,” and “contour” are significantly interrelated and related to clients’ mental health, i.e. psychopathology, psychological flexibility, experiential avoidance, and adaptability. These findings give insight in the diagnostic value of art products and how they may add to clients’ verbal expression and indicate their potential to benefit from therapy.